Impact of Tourism Activities on Water Pollution and Tourist Attractions in Koh Larn Beach Pattaya, Thailand - Nantawit Boondesh, Pornthip Layanan, R. Hazanal Rashid Khan, Warairat Somphong, Somporn Naklang (International Journal of Advanced Science and Technology, 2020)
Tourism industry potentially growing rapidly in different parts of the world. It plays an important role in socio-economic, cultural development and sustainable development. According to the tourism statistics of Thailand, 38.27 million tourists have been arrived in the year of 2018 with increased up 7.5% from 2017 and which has significantly contributed to the country’s economy. However, tourism sector induces negative impacts on environment, and culture. The study aimed to elucidate the factors encourages to visit Koh Larn beach. A total of 95 tourists were randomly selected as study subjects. Survey was conducted by using questionnaire. The results of the study revealed and evidenced that the visitors take into consider the following factors to choose the destination such as natural beauty of the destination. However, the selection of destination point based on pleasant climate, beautiful beaches accommodation, food, safety, convenience, recreation, and other basic facilities available at the desired destination points. The study results revealed that the tourism activities may impact on water quality, water pollution such as increases the heavy metals concentrations ultimately it influences the aquatic life, food chain finally mammals will affect with wide range of pollutants.